Langerhans cell histiocytosis in childhood - review, symptoms in the oral cavity, differential diagnosis and report of two cases - Merglová, Vlasta; Hrušák, Daniel; Boudová, Ludmila; Mukenšnabl, Petr; Valentová, Eva; Hostička, Lubor (Journal of cranio-maxillo-facial surgery, 2014)
BACKGROUND: Langerhans cell histiocytosis is a rare disease characterized by monoclonal proliferation and migration of special dendritic cells. This disease primarily affects bones, but occurs less frequently in other organ systems or may manifest as a multisystem disease. CASE REPORTS: Extraoral and intraoral symptoms of Langerhans cell histiocytosis are described in a 13-month-old female and a 5-month-old male infant. Dermatitis was found on the scalp, abdomen, flexures and in intertrigineous areas in both patients. The intraoral examination of the 13-month-old infant showed premature eruption of all maxillary deciduous molars, loosening and significant damage of periodontal tissues (gingivitis with bleeding, swelling of palatal mucosa, periodontal pockets) resembling severe periodontitis. In the oral cavity of the 5-month-old predentate infant bilateral swellings of maxillary alveolar mucosa with deep ulcerations were seen. The oral and skin symptoms in both infants were indications for biopsy. Langerhans cell histiocytosis was confirmed histologically and immunohistochemically. CONCLUSION: Oral findings in Langerhans cell histiocytosis may be the only clinical symptom of the disease; therefore the role of dentists in establishing diagnosis is very important.
Keywords: Stomatitis; prořezávání zubů; vředy v ústech; Follow-Up Studies; dermatitida; histiocytóza z Langerhansových buněk; Biopsy; Humans; lidé; Periodontal Pocket; Oral Ulcer; Scalp Dermatoses; následné studie; Langerhans cell histiocytosis; Histiocytosis, Langerhans-Cell; Molar; Granulomatous gingivitis; Bone lesions; nemoci úst; Female; Diagnosis, Differential; Male; Infants; stomatitida; krvácení dásní; Tooth, Deciduous; gingivitida; kojenec; mužské pohlaví; Mouth Diseases; Infant; zuby mléčné; Gingivitis; ženské pohlaví; Periodontitis; parodontální chobot; moláry; parodontitida; dermatózy skalpu; Dermatitis; Gingival Hemorrhage; diferenciální diagnóza; Tooth Eruption; biopsie